2015
DOI: 10.1186/s13028-015-0183-2
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and “Knowledge, Attitudes and Practices” (KAPs) survey of endemic ovine brucellosis in Egypt

Abstract: BackgroundBetween February and July 2014, a cross-sectional study to estimate the seroprevalence of brucellosis in sheep in the Kafrelsheikh district of Egypt was carried out, together with a survey of knowledge, attitudes and practices (KAPs) among local shepherds. A total of 273 serum samples were collected from 28 sheep flocks in 10 villages within the study area. These samples were analysed by the Rose Bengal Plate test (RBPT) test, with all positive samples being confirmed by complement fixation test (CFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 18 publications
5
53
0
Order By: Relevance
“…In our study, herders with a higher level of knowledge were more likely to correctly dispose of aborted fetuses and birth materials compared to those with a lower level of knowledge. In Egypt, lack of knowledge regarding disease transmission was associated with throwing aborted materials into water canals (Hegazy et al, ), consistent with findings from this research. Also, there was a difference between the two provinces.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, herders with a higher level of knowledge were more likely to correctly dispose of aborted fetuses and birth materials compared to those with a lower level of knowledge. In Egypt, lack of knowledge regarding disease transmission was associated with throwing aborted materials into water canals (Hegazy et al, ), consistent with findings from this research. Also, there was a difference between the two provinces.…”
Section: Discussionsupporting
confidence: 89%
“…In our results, around half of herders reported that they bury aborted fetuses and birth materials. This practice was highly prevalent (94%) among Tajikistan's dairy farmers (Lindahl et al, ), but not in Pakistan (Arif et al, ), Egypt (Hegazy et al, ) or Jordan (Musallam et al, ). In our study, herders with a higher level of knowledge were more likely to correctly dispose of aborted fetuses and birth materials compared to those with a lower level of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these libraries, the size distribution followed the RNA length distribution reported in other equine and bovine serum samples [19, 20], with the majority of the reads (78 %) falling into piwi-interacting RNA region (30–32 nt) and with a smaller peak (4 %) in the mature miRNA region (22–23 nt). On the other hand, after removal of low-quality reads, the flanking linker and primer sequences, SOLiD data comprised 8 M reads on average with mean per sequence quality of 27 in the Phred scale per library.…”
Section: Resultsmentioning
confidence: 85%
“…The absorbance in 200 μl of serum was measured at 414 nm wavelength, which is the length of maximum absorbance for haemoglobin [55, 56]. The RNA was extracted from 2 ml of serum using miRNeasy serum/plasma kit as described in [20]. The concentration of RNA extracted was measured with Qubit RNA High Sensitivity kit and ranged from 2 to 428 ng/μl (20 ng/μl on average).…”
Section: Methodsmentioning
confidence: 99%